Conceptual Framework of Digital Amanah: Blockchain as Trust Infrastructure and Stablecoin as Value Instrument in Islamic Economics : a Systematic Literature Review - Ahmad Nouruzzaman; Akbar Sabami; Humaidi; Abd. Kadir Arno; Muh. Yusril Mantovani; Ahmad Syawal Senong Pakata (Prodi Hukum Ekonomi Syariah, Fakultas Syariah, IAIN Palopo, 2026)
Purpose – This article develops a conceptual framework of digital amanah for Islamic digital economics by examining how trust should be institutionalized across the normative, infrastructural, and instrumental layers of digital economic systems. It specifically analyzes how amanah functions as an ethical-institutional principle, how blockchain can be positioned as a trust infrastructure, and how stablecoins can be evaluated as instruments of value protection within Islamic economics. Method – This study employs a systematic literature review reported in line with PRISMA 2020 and supported by PRISMA-S. The review draws on 50 peer-reviewed journal articles published between January 2015 and March 2026, identified through searches in Scopus, Web of Science Core Collection, and Dimensions, and synthesized through qualitative thematic analysis. Result – The review shows three main findings. First, amanah in Islamic economics should be understood not merely as an individual moral quality, but as an ethical-institutional principle requiring transparency, accountability, stakeholder protection, and the safeguarding of value and rights. Second, blockchain can function as an infrastructure of digital amanah only when its traceability, verifiability, and auditability are supported by credible governance and effective oversight. Third, stablecoins can be regarded as digital instruments of amanah only when they preserve value substantively through transparent reserves, clear redemption rights, and governance arrangements that protect users from excessive uncertainty and institutional failure. The article further formulates theoretical propositions explaining the conditional relationship between amanah, blockchain governance, stablecoin reserve credibility, and Islamic economic legitimacy. Implication – The findings suggest that Islamic digital finance should be evaluated not only in terms of permissibility or technical utility, but also in terms of how digital systems protect value, rights, and public trust under accountable governance.